Atmospheric Precipitations, Hailstone and Rainwater, as a Novel Source of Streptomyces Producing Bioactive Natural Products - Sarmiento-Vizcaíno, Aida; Espadas, Julia; Martín, Jesús; Braña, Alfredo F.; Reyes, Fernando; García, Luis A.; Blanco, Gloria (Frontiers in Microbiology, 2018)
A cultivation-dependent approach revealed that highly diverse populations of Streptomyces were present in atmospheric precipitations from a hailstorm event sampled in February 2016 in the Cantabrian Sea coast, North of Spain. A total of 29 bioactive Streptomyces strains isolated from small samples of hailstone and rainwater, collected from this hailstorm event, were studied here. Taxonomic identification by 16S rRNA sequencing revealed more than 20 different Streptomyces species, with their closest homologs displaying mainly oceanic but also terrestrial origins. Backward trajectory analysis revealed that the air-mass sources of the hailstorm event, with North Western winds, were originated in the Arctic Ocean (West Greenland and North Iceland) and Canada (Labrador), depending on the altitude. After travelling across the North Atlantic Ocean during four days the air mass reached Europe and precipitated as hailstone and rain water at the sampling place in Spain. The finding of Streptomyces species able to survive and disperse through the atmosphere increases our knowledge of the biogeography of genus Streptomyces on Earth, and reinforces our previous dispersion model, suggesting a generalized feature for the genus which could have been essential in his evolution. This unique atmospheric-derived Streptomyces collection was screened for production of bioactive secondary metabolites. Analyses of isolates ethyl acetate extracts by LC-UV-MS and further database comparison revealed an extraordinary diversity of bioactive natural products. One hundred molecules were identified, mostly displaying contrasted antibiotic and antitumor/cytotoxic activities, but also antiparasitic, antiviral, anti-inflammatory, neuroprotector, and insecticide properties. More interestingly, 38 molecules not identified in natural products databases might represent new natural products. Our results revealed for the first time an extraordinary diversity of Streptomyces species in the atmosphere able to produce an extraordinary repertoire of bioactive molecules, thus providing a very promising source for the discovery of novel pharmaceutical natural products.